Antibacterial Activity Test of Matoa (Pometia pinnata) Leaves Ethanol Extract Against Salmonella typhi and Bacillus subtilis - Pagarra, Halifah; Taiyeb , Mushawwir; Junda , Muhammad; Musawira; Muhammad Naufal Syaiful Haq; Handayani , Resti (Bionature, 2025)
This study aims to determine the antimicrobial activity of ethanol extract of matoa leaves (Pometia pinnata) against Salmonella typhi and Bacillus subtilis bacteria. This study began with preparing raw materials in the form of matoa leaves and then extracting the matoa leaves using the maceration method with 70% solvent. After that, the antimicrobial activity test was carried out using the disc diffusion method with four concentration variations, namely 5%, 7.5%, 10%, and 12.5% with a positive control in the form of 50 ppm amoxicillin and a negative control using distilled water, each treatment using three replications. The results in the form of inhibition zones formed were measured using calipers. The data obtained were then analyzed using SPSS 30 with the ANOVA test and further tests in the form of tests. The test results showed that 70% ethanol extract of matoa leaves had an effect on inhibiting the growth of Salmonella typhi and Bacillus subtilis bacteria. The largest inhibition zone in Salmonella typhi was found at a concentration of 7.5% with a diameter of 16.87 mm, while in Bacillus subtilis it was found at a concentration of 12.5% with a diameter of 12.22 mm. Keywords: Pometia pinnata, Antimicrobial activity, Salmonella typhi, Bacillus subtilis